Implementation of OpenIdconnect and OAuth 2.0 to create SSO for educational institutes - Sujanani, Tarun; Vinod, Smitha (International Journal of Engineering and Technology, 2018)
Increase in the number of users is directly proportional to the need of verifying them. This means that any user using any website or application has to be authenticated first; this leads to the creation of multiple credentials of one user. Now if these different websites or applications are connected or belong to one single organization like a college or school, a lot of redundancy of data is there. Along with this, each user has to remember a wide range of credentials for different applications/websites. So in this paper, we address the issue of redundancy and user related problems by introducing SSO using OpenId Connect in educational institutes. We aim to mark the difference between the traditional system and proposed login by testing it on a group of users.